Numerical Modelling Point-to-Plane of Negative Corona Discharge in N2 Under Non-Uniform Electric Field. (June 2015) - Ferouani, A. K.; Lemerini, M.; Merad, L.; Houalef, M.
Abstract The paper presents a simulation model of the negative corona discharge in N2 under various pressures. The simulated discharge is of a negative point-to-plane mass type, with an inter-electrode separation distance of 20 mm and a symmetry about the axis of discharge. This simulation investigates the behavior of the neutral density and temperature for different pressures in the range of 0.1–10.0 bar. The spatial and temporal evolution of the neutral gas is analyzed based upon the equations of continuity, momentum and energy in a two-dimensional cylindrical geometry model. For that geometry of the system, the FCT (Flux Corrected Transport) technique was adopted. The results show that the pressure plays a significant role of the neutrals dynamics.